The Effectiveness of the Cooperative Learning Model of the TGT (Teams Games Tournament) Type in Improving Arabic Vocabulary Acquisition - Jannah, Miftahul; Rofiq, Ainur; Baihaqi, M.; Jundi, Ahmad; Robbaniyah, Nabilah; Hudzaifah, M. (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2025)
Purpose- The purpose of this study is to analyze the effectiveness of the cooperative learning model of the TGT (Teams Games Tournament) type in improving Arabic vocabulary acquisition among eighth-grade students at MTsN 2 Kota Surabaya. Design/Methodology/Approach- This research employed a quantitative method with a quasi-experimental approach using a one-group pretest-posttest design. The study involved 33 eighth-grade students as research participants. Data were collected through objective tests consisting of multiple-choice and essay questions administered before and after the implementation of the TGT model. The data were analyzed using descriptive statistics and a paired sample t-test. Findings- The results revealed a significant increase in students’ average scores from 55.30 in the pretest to 93.00 in the posttest. The t-value of -12.993 with a significance level of 0.000 < 0.05 indicates that the null hypothesis (H₀) is rejected, and the alternative hypothesis (H₁) is accepted. These findings provide strong evidence that the TGT model is effective in enhancing Arabic vocabulary mastery. Research Limitation/Implications- The implications of these findings suggest that the use of the TGT learning model can serve as an innovative strategy in Arabic language instruction at the secondary level. It is hoped that the results of this study will serve as a reference for educators in selecting more interactive, collaborative, and effective teaching approaches that significantly improve students' learning outcomes.